Factors controlling fluoride contents of groundwater in north-central and northwestern Sri Lanka - Young, Sansfica M.; Pitawala, A.; Ishiga, H. (Springer-Verlag, 2011)
Chemical characterization has been made of groundwater bodies at 294 locations in four village districts in north-central and northwestern Sri Lanka, with special focus on fluorine contamination. High fluoride contents in groundwater are becoming a major problem in the dry zone of Sri Lanka, and dental fluorosis and renal failures are widespread. Field measurements of temperature, pH, and electrical conductivity were made during sampling. Chem ical analyses of the water samples were later made using atomic absorption spectroscopy, spectrophotometry, and titration. Fluoride concentrations in the study area vary from 0.01 to 4.34 mg/l, and depend on pH and the concentrations of Na, Ca, and HCO3 -. Basement rocks including horn blende biotite gneiss, biotite gneiss, and granitic gneiss seem to have contributed to the anomalous concentrations of fluoride in the groundwater. Longer residence time in aquifers within fractured crystalline bedrocks may enhance fluoride levels in the groundwater in these areas. In addition, elevated fluoride concentrations in shallow groundwater in intensive agricultural areas appear to be related to the leaching of fluoride from soils due to successive irrigation.
Keywords: Groundwater; Fluoride; Granitic gneiss; Agriculture Soil